2021
DOI: 10.1177/14759217211008619
|View full text |Cite
|
Sign up to set email alerts
|

A portable bolt-loosening detection system with piezoelectric-based nondestructive method and artificial neural networks

Abstract: In general, the bolted joints that connect and secure components together can be easily spotted in our surroundings. This joining method has been commonly used in various areas of engineering (e.g. aerospace, civil, and mechanical engineering) as it has been proven one of the most effective means to join parts together. Although it has its advantages, the vibration that bolted structures endure during service ultimately causes the bolts to loosen. This can, in turn, have a negative effect on the structure’s sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…e sensor selected is the ADXL321MEMS acceleration sensor. However, due to the limitations of the experimental conditions and the completion of the project, the actual aircraft condition monitoring experiment has not been carried out at present [5]. Hu et al adopted the wireless sensor network mechanical equipment monitoring system designed by themselves and applied it to 4 QUY50C crawler cranes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e sensor selected is the ADXL321MEMS acceleration sensor. However, due to the limitations of the experimental conditions and the completion of the project, the actual aircraft condition monitoring experiment has not been carried out at present [5]. Hu et al adopted the wireless sensor network mechanical equipment monitoring system designed by themselves and applied it to 4 QUY50C crawler cranes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the accuracy of PNN improved from 72.2% to 94.4% by smoothing the signal using the centered moving average method with 20 data points. Further, Na 145 created a low-cost monitoring system using a re-attachable PZT device in conjunction with a PNN to detect bolt looseness. They extracted impedance signals from three different-sized bolts and quantified them using statistical metrics, that is, RMSD and MAPD.…”
Section: Mechanical Properties Ofmentioning
confidence: 99%
“…20 Among them, piezoelectric sensors based on the piezoelectric effect have become one of the key SHM technologies owing to their high sensitivity, simple control system, light weight, low energy consumption, as well as dual sensing and actuation. 21,22 Thanks to the superior performance of piezoelectric sensing technology, the research on health monitoring of bolted joints supported by the piezoelectric vibration method, 23 ultrasonic guided wave (UGW) technique, 24 and electromechanical impedance (EMI) method 25 has burst into a series of valuable achievements in recent years. 2636 Earlier, research on piezoelectric sensing-based health monitoring techniques for bolted joints focused on investigating the feasibility and effectiveness of piezoelectric sensing in various modes of damage monitoring.…”
Section: Introductionmentioning
confidence: 99%